(untitled) (Research, Society and Development, 2021)
The inflammatory process involves several vascular changes controlled by inflammation mediators. Vascular changes are increased vasodilation, increased vascular permeability, decreased local blood flow. The inflammatory process also induces leukocyte mobilization and migration from its storage sites to the site of action. During the process there is an increase in hepatic metabolism that leads to increased levels of acute phase proteins: fibrinogen, C-reactive protein, among others. In this work, parameters in the blood count were measured, such as total plasma protein, fibrinogen and ESR to measure the degree of inflammation, the red series was evaluated taking into account the presence of anemia and its type and the white series classifying leukocytosis and why the appearance of each of them. To obtain these results, a complete blood count, total plasma protein and erythrocyte sedimentation rate were performed using the Westergren method. The main objective of this work is to measure the erythrocyte sedimentation rate, making a comparison between animals with high ESR and animals with ESR within the reference values, observing the recovery time and degree of inflammation of the patient. In the results, we were able to perceive simple changes in the ESR with animals with inflammatory processes, making that, in the near future, this parameter also be used as a complementary exam to assist in the diagnosis of diseases that involve the inflammatory process itself. It is concluded that the ESR is a valid test in inflammatory processes, even with its low specificity.